Team-reflection: the missing link in co-teaching teams. Issue 2 (2nd April 2016) - Fluijt, D.; Bakker, C.; Struyf, E.
Abstract: In literature, co-teaching is mostly defined as an instrumental and pedagogical means delivered by collaborating special and regular teachers, from which students with and without special educational needs benefit in regular schools. The importance of a shared vision on the part of members of co-teaching teams as to what they consider as good education for students is not mentioned in definitions of co-teaching. The authors argue that sense-making by reflection about what can be considered as good education – good teaching and good learning – is essential when co-teachers want to understand or change their practice or relationship with their partner. We reviewed 17 articles about co-teaching teams' professional development and identified that challenges to co-teachers' professionalisation mostly were directed to interpersonal and normative aspects of development in co-teaching teams. We elaborate on five distinguished movements that can bring about change in teacher professionalism. These movements correspond to the challenges retrieved from the literature review and can be used to contribute to move toward a new perspective on professionalism of co-teachers. A contemporary definition of co-teaching is proposed because former definitions do not suffice to express the value of constructing a shared vision on good teaching and learning. We argue that team-reflection is the missing link in terms of enhancing normative professionalism of co-teaching teams and recommend that further research should be conducted to value team-reflection as a means to overcome challenges of co-teaching teams.